Modeling of introduction populations as a method of ex situ protection of rare species of plants - Melnyk, V.I.; Gritsenko, V.V.; Kushnir, N.V.; Nehrash, Yu.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The experience of the introduction of rare and endangered species of plants in M.M. Grishko National Botanical Garden of the NAS of Ukraine is analyzed. A new method of floristic diversity ex situ protection by means of the modeling of populations in forest and steppe phytocenoses is proposed.